Dervîş Muhammed Şifâyî’nin Şerh-i Şebistân-i Hayâl’indeki Muammâ Çözüm Yöntemleri Üzerine Bir İnceleme / An Investigation on Dilemma Resolution Methods in the Sharh Shabistan Khayal of Darwish Muhammad Shifayi - Özdemir, Mehmet (Journal of History Culture and Art Research, 2017)
Abstract Darwish Muhammad Shifayi was born in early seventeenth century, and has been known as the commentator on Masnawi with his commentary on the first two volumes of the Rumi’s Masnawi. This famous commentator also had other works like Hadiyyet al-Fukara in which he translated Esma al-Hüsnâ, which was originally Persian and was translated into Turkish by him; Hadiyye-i Rahmat in which he wrote about Islam, mysticism and religious cults; and Sharh Shabistan Khayal in which he commented on the work of Fattah al-Nishabûrî called Shabistan Khayal. A critical text study was conducted on the first volume of his work with the name Sharh-i Masnawi and the critical text study is being conducted at present time about the second volume of this work and about Hadiyyat al-Fukarâ. There are no studies on Sharh Shabistan Khayal and on Hadiyye-i Rahmat, which is currently not available in Turkey. In this study, the work called Sharh Shabistan Khayal located in Süleymaniye Library Serez 2656 number will be introduced, the purpose of the commentator will be explained, and the commentary method will be dealt with. In Shabistan Khayal, which was originally written in Persian, issues on religion and life were handled with the dilemma style by using letter and word games. For this reason, when determining the commentary method of such a text, the translation and commentary of Persian expressions and the solution ways of the dilemmas must be considered. Based on this context, when explaining the commentary method of the commentator, the translation and commentary of the Persian text will be dealt with firstly; and the dilemma resolution methods such as amel-i tahsîlî, amel-i tekmîlî, amel-i teshîlî, amel-i tezyîlî will be dealt with in the second section under the title of “Art”. Öz On yedinci yüzyılın başında dünyaya gelen Dervîş Muhammed Şifâyî, Mevlânâ’nın Mesnevî’sinin ilk iki cildine yaptığı şerhle Mesnevî şarihi olarak tanınmıştır. Şarihin bundan başka aslı Farsça olan iki Esmâ-yı Hüsnâ şerhini Türkçeye tercüme ettiği Hediyyetü’l-Fukarâ, İslam dini, tasavvuf ve tarikatlara dair kaleme aldığı Hediyye-yi Rahmet ve Fettâh-ı Nişâbûrî’nin Şebistân-ı Hayâl adlı eserini şerh ettiği Şerh-i Şebistân-ı Hayâl adlı eserleri vardır. Bu eserlerden Şerh-i Mesnevî’nin birinci cildi üzerinde tenkitli metin çalışması yapılmış, söz konusu eserin ikinci cildi ve Hediyyetü’l-Fukarâ adlı eser üzerinde tenkitli metin çalışmaları yapılmaktadır. Şerh-i Şebistân-ı Hayâl ve yurt dışında bulunduğu için henüz temin edilemeyen Hediyye-yi Rahmet adlı eserlerle ilgili bir çalışma yoktur. Bu makalede, Süleymaniye Kütüphanesi Serez 2656 numarada bulunan Şerh-i Şebistân-ı Hayâl adlı eser tanıtılıp şarihin maksadını izahtan sonra şerh yöntemi üzerinde durulacaktır. Aslı Farsça olan Şebistân-ı Hayâl’de, din ve hayata dair konular harf ve kelime oyunları vasıtasıyla muammâ tarzında ele alınmıştır. Dolayısıyla böyle bir metnin şerh yöntemini belirlerken hem Farsça ifadelerin tercüme ve şerhi hem de muammâların çözüm şekilleri göz önünde bulundurulmalıdır. Bu düşünceden hareketle şarihin şerh yöntemi ele alınırken öncelikle Farsça metnin tercüme ve şerhi, ikinci olarak da “sanat” başlığı altında, muammâların halledildiği bölümde kullanılan amel-i tahsîlî, amel-i tekmîlî, amel-i teshîlî, amel-i tezyîlî gibi muammâ çözüm yöntemleri üzerinde durulacaktır.